Pro (With Caution): Extended oncologic indications in liver transplantation. Issue 1 (8th December 2017) - Mazzaferro, Vincenzo; Battiston, Carlo; Sposito, Carlo
Abstract : The success of liver transplantation (LT) in curing cancer (particularly hepatocellular carcinoma and hepatic metastases from neuroendocrine tumors) is based on the augmented oncologic potentials of the total hepatectomy and on restrictive criteria applied to patient selection. Consensus on the grade of expansion of conventional limits and implementation of alternative indications to LT (cholangiocarcinoma and metastases from colorectal cancer) has not been reached. On top of regional/local conditions for wait‐list dynamics and organ availability, expanded cancer indications for LT should be explored with caution. Prospective investigations should rely on staging protocols predicting the exclusive hepatic location of cancer; restrictions on clinical conditions, tumor biology, and molecular profile, including the response to neoadjuvant therapies; confirmed tumor nonresectability with curative intent; sufficient life span of the transplant candidates to assess survival and transplant benefit; and use of marginal and extended criteria donors. In conclusion, the arguments supporting moderately loosened criteria for cancer seem more valid today than in the past. Transplant oncology is likely to represent a leading field in the near future, also because comorbidities and transplant‐related causes of death are better managed and often eliminated. Liver Transplantation 24 98–103 2018 AASLD.